Cross-Site Reliability of Human Induced Pluripotent stem cell-derived Cardiomyocyte Based Safety Assays Using Microelectrode Arrays: Results from a Blinded CiPA Pilot Study. (27th April 2018) - Millard, Daniel; Dang, Qianyu; Shi, Hong; Zhang, Xiaou; Strock, Chris; Kraushaar, Udo; Zeng, Haoyu; Levesque, Paul; Lu, Hua-Rong; Guillon, Jean-Michel; Wu, Joseph C; Li, Yingxin; et al.
Abstract: Recent in vitro cardiac safety studies demonstrate the ability of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) to detect electrophysiologic effects of drugs. However, variability contributed by unique approaches, procedures, cell lines, and reagents across laboratories makes comparisons of results difficult, leading to uncertainty about the role of hiPSC-CMs in defining proarrhythmic risk in drug discovery and regulatory submissions. A blinded pilot study was conducted to evaluate the electrophysiologic effects of 8 well-characterized drugs on 4 cardiomyocyte lines using a standardized protocol across 3 microelectrode array platforms (18 individual studies). Drugs were selected to define assay sensitivity of prominent repolarizing currents (E-4031 for I Kr, JNJ303 for I Ks ) and depolarizing currents (nifedipine for I CaL, mexiletine for I Na ) as well as drugs affecting multichannel block (flecainide, moxifloxacin, quinidine, and ranolazine). Inclusion criteria for final analysis was based on demonstrated sensitivity to I Kr block (20% prolongation with E-4031) and L-type calcium current block (20% shortening with nifedipine). Despite differences in baseline characteristics across cardiomyocyte lines, multiple sites, and instrument platforms, 10 of 18 studies demonstrated adequate sensitivity to I Kr block with E-4031 and I CaL block with nifedipine for inclusion in the final analysis. Concentration-dependent effects on repolarization were observed with this qualified data set consistent with known ionic mechanisms of single and multichannel blocking drugs. hiPSC-CMs can detect repolarization effects elicited by single and multichannel blocking drugs after defining pharmacologic sensitivity to I Kr and I CaL block, supporting further validation efforts using hiPSC-CMs for cardiac safety studies.